2013
DOI: 10.1038/ncomms2795
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a robust single axis of cell polarity by coupling multiple positive feedback loops

Abstract: Establishment of cell polarity—or symmetry breaking—relies on local accumulation of polarity regulators. Although simple positive feedback is sufficient to drive symmetry breaking, it is highly sensitive to stochastic fluctuations typical for living cells. Here, by integrating mathematical modelling with quantitative experimental validations, we show that in the yeast Saccharomyces cerevisiae a combination of actin- and guanine nucleotide dissociation inhibitor-dependent recycling of the central polarity regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
163
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(180 citation statements)
references
References 59 publications
12
163
3
Order By: Relevance
“…For instance, Spa2 and Gic2 are involved in Bni1 recruitment to sites of cell polarity and/or activation, yet their deletion shows genetic interactions with BNI1 deletion (Fujiwara et al 1998;Jaquenoud and Peter 2000;Sagot et al 2002a;Chen et al 2012). In this context it is worth considering that effectors of the Cdc42 GTPase, which include many formin regulators and formins themselves, are part of positive feedback loops that enhance Cdc42 activation at the polarity site, thereby contributing to the establishment of a robust polarity axis (Wedlich-Soldner et al 2003;Wedlich-Soldner et al 2004;Kozubowski et al 2008;Freisinger et al 2013). Thus, some of the genetic interactions reported in the literature could be ascribed to polarity defects, rather than to problems in actin organization.…”
Section: Formin Regulation By Dma Ubiquitin Ligases 213mentioning
confidence: 99%
“…For instance, Spa2 and Gic2 are involved in Bni1 recruitment to sites of cell polarity and/or activation, yet their deletion shows genetic interactions with BNI1 deletion (Fujiwara et al 1998;Jaquenoud and Peter 2000;Sagot et al 2002a;Chen et al 2012). In this context it is worth considering that effectors of the Cdc42 GTPase, which include many formin regulators and formins themselves, are part of positive feedback loops that enhance Cdc42 activation at the polarity site, thereby contributing to the establishment of a robust polarity axis (Wedlich-Soldner et al 2003;Wedlich-Soldner et al 2004;Kozubowski et al 2008;Freisinger et al 2013). Thus, some of the genetic interactions reported in the literature could be ascribed to polarity defects, rather than to problems in actin organization.…”
Section: Formin Regulation By Dma Ubiquitin Ligases 213mentioning
confidence: 99%
“…Here, bud emergence occurs towards the cell membrane with depolarized potential [140], probably coordinated by plasma membrane lipid polarization [138].…”
Section: Defining Singularities In Cellsmentioning
confidence: 99%
“…Numerous studies have established a mechanism in which recruitment of Cdc42 to the site of polarization (where activated, GTP-bound Cdc42 seems to laterally diffuse, [135]) requires actin-mediated transport of vesicle-bound Cdc42 [136] or GTPase-activating protein (GAP)-mediated recruitment of Cdc42 [137]. In addition, Cdc42 cycling between GTP-bound/active and GDP-bound/inactive states is crucial for polarization, which is controlled by a guanine nucleotide exchange factor (GEF, Cdc24), GAPs (Bem2, Bem3, Rga1, Rga2), a Rho-guanine nucleotide dissociation inhibitor (GDI, Rdi1) [138], and plasma membrane lipid anisotropy [139] (Figure 4d). Recent work has shown that actin-mediated recycling of Cdc42 induces robust symmetry breaking but does not restrict polarization to a single site [6].…”
Section: Defining Singularities In Cellsmentioning
confidence: 99%
“…Another form of symmetry breaking refers to the formation of a polar axis without any detectable, preexisting landmark (WedlichSoldner et al 2003). Although a full consensus has yet to be reached regarding the specific details of this form of symmetry breaking (Johnson et al 2011), it does involve the simultaneous action of multiple feedback loops that direct the accumulation of the activated form of the Cdc42 GTPase at a discrete site on the cell surface (Freisinger et al 2013). Such feedback loops can be regulated to permit formation of multiple polarity axes based on studies in S. cerevisiae (Wu and Lew 2013).…”
mentioning
confidence: 99%